2012
DOI: 10.5713/ajas.2012.12249
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Replacing Soybean Meal with Fermented Rapeseed Meal on Performance, Serum Biochemical Variables and Intestinal Morphology of Broilers

Abstract: This trial was performed to study the effects of replacing soybean meal (SBM) with fermented rapeseed meal (RSM) on growth performance, serum biochemistry variable and intestinal morphology of broilers. A total of 640 d-old Arbor Acres broiler chicks were randomly allocated to 4 dietary treatments, 4 pens per treatment and 40 birds per pen for a 6-wk feeding trial. In the four treatment groups, fermented RSM replaced soybean meal at 0, 5, 10, and 15%, respectively. On 21 d and 42 d, two birds from each pen wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
50
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 32 publications
15
50
2
3
Order By: Relevance
“…Long villus height and intact mucosal integrity are essential for nutrient digestion and absorption as well as prevention of invasion of intestinal tissues by pathogenic microbes. Similar findings were reported when fermented rapeseed was fed to broilers where intestinal villus height and villus-to-crypt ratio showed significant improvements [13,37,38]. Feeding of fermented soybean to weaned piglets [39] and Japanese quail [40] also demonstrated significant improvement in villus height but reduced crypt depth along the intestine.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Long villus height and intact mucosal integrity are essential for nutrient digestion and absorption as well as prevention of invasion of intestinal tissues by pathogenic microbes. Similar findings were reported when fermented rapeseed was fed to broilers where intestinal villus height and villus-to-crypt ratio showed significant improvements [13,37,38]. Feeding of fermented soybean to weaned piglets [39] and Japanese quail [40] also demonstrated significant improvement in villus height but reduced crypt depth along the intestine.…”
Section: Discussionsupporting
confidence: 76%
“…Conversely, levels of serum immunoglobulins (IgG, IgM, IgA) and IL-6 were increased in response to lower doses (8% or 10% FRM), while the inclusion of AN enhanced IgG but reduced the rests. A study showed that feeding of fermented products, such as the soybean meal, to weaned piglets significantly improved mucosal or systemic immunoglobulins [38,39,54,55]. The discrepancy between increased immunoglobulins and WBC counts could be related to the preferential activation of the adaptive immune responses, which culminate in the increment of immunoglobulins.…”
Section: Discussionmentioning
confidence: 99%
“…Fermentation of RSM with Lactobacillus fermentum and B. subtilis increased CP, Lys, sulfur AA and considerably decreased isothiocyanates (from 108.7 to 13.1 mmol/kg) (Xu et al, 2012). In the present study none of the two processes modified the AA content of the peas, except a reduction in CF and a slight increase in CP.…”
Section: Discussioncontrasting
confidence: 53%
“…Broilers fed diets containing 10% fermented RSM (with L. fermentum, Enterococcus faecium, Saccharomyces cerevisae and B. subtilis) had better BWG and FCR compared with those fed diets containing 10% native RSM (Chiang et al, 2010). The BWG and FCR of broilers fed diets containing 15% fermented RSM were worse than those received feed containing 0, 5 and 10% fermented RSM, while the other three groups (0%, 5% and 10%) were similar (Xu et al, 2012).…”
Section: Discussionmentioning
confidence: 89%
“…Recent research has shown that microbial fermentation can effectively reduce the content of these anti‐nutrient factors and improve palatability . Therefore, research has focused on adding fermented RSM (FRSM) as a protein source to animal feed, which has led to promising results . With the emergence of meal from double‐low rapeseed varieties with their lower levels of erucic acid and glucolisinates and the maturation of fermentation technology, the proportion of FRSM used in animal feed has increased significantly.…”
Section: Introductionmentioning
confidence: 99%